Insecticidal and Enzyme Inhibitory Activities of Isothiocyanates against Red Imported Fire Ants, Solenopsis invicta - Yuzhe Du; Michael J. Grodowitz; Jian Chen (Biomolecules, 2020)
Contact and fumigation toxicity of four isothiocyanates (ITCs), including allyl isothiocyanate (AITC), 3-butenyl isothiocyanate (3BITC), 3-(methylthio) propyl isothiocyanate (3MPITC) and 2-phenylethyl isothiocyanate (2PEITC), were evaluated against the red imported fire ant worker, Solenopsis invicta Buren. 2PEITC and 3MPITC exhibited strong contact toxicity. The median lethal dose (LD50)value of AITC, 2PEITC and 3MPITC were 7.99, 2.36 and 2.09 µg/ant respectively. In addition, AITC and 3MPITC also showed strong fumigation toxicity but not 2PEITC. The median lethal concentration (LC50) values of AITC and 3MPITC were 32.49 and 57.6 µg/L, respectively. In contrast, 3BITC did not exhibit any contact and fumigation toxicity even at 100 μg/μL. Esterase (EST), glutathione S-transferase (GST) and acetylcholinesterase (AChE)-inhibiting activities were assessed for three ITCs in S. invicta workers. All three ITCs inhibited both EST and GST activities but not AChE. The in vitro half maximal inhibitory concentration (IC50)values of AITC, 2PEITC and 3MPITC for GST were 3.32, 0.61 and 0.66 µg/µL, respectively. These results suggested that naturally occurring ITCs might be potentially useful for developing fire ants control products.